1979
DOI: 10.1271/bbb1961.43.1399
|View full text |Cite
|
Sign up to set email alerts
|

Production of .BETA.-phenethyl alcohol from styrene by Pseudomonas 305-STR-1-4.

Abstract: The productivity of ƒÀ-phenethyl alcohol (a-PA) from styrene by Pseudomonas 305-STR-1-4 was examined under various conditions. Under the optimum condition, 3.27mg/ml of fl-PA was produced from 20mg/ml of styrene. The metabolic inhibitor, pyrazole, aided ineffectively producing a-PA more reliably and promptly.ƒÀ-PA was extracted from the culture broth and purified to a semi-viscous, light-yellow liquid with a rose-like fragrance. Recovery was 90% and purity was 99.4%. IR spectrum of this liquid was identical wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Shira '~ and Hisatsuka (1979) reported the role of styrene oxide as an intermediate metabolite in the oxidation of styrene to 2-phenylethanol by Pseudomonas 305-STR-1-4. Hartmans et al (1989Hartmans et al ( , 1990) discussed, with more details, the enzymes involved in the degradation of styrene oxide and 2-phenylethanol by Xanthobacter 124X.…”
Section: Introductionmentioning
confidence: 99%
“…Shira '~ and Hisatsuka (1979) reported the role of styrene oxide as an intermediate metabolite in the oxidation of styrene to 2-phenylethanol by Pseudomonas 305-STR-1-4. Hartmans et al (1989Hartmans et al ( , 1990) discussed, with more details, the enzymes involved in the degradation of styrene oxide and 2-phenylethanol by Xanthobacter 124X.…”
Section: Introductionmentioning
confidence: 99%
“…Styrene (vinyl-benzene) is a polymer and it is a natural component in plants. It is aerobically degradable by different types of bacteria (Grbic-Galic, 1990;Omori, 1974Omori, , 1975Shirai, 1979;Sielicki, 1978). It has also been shown to be degraded by an anaerobic consortium of micro-organisms (Grbic-Galic, 1990).…”
Section: Low and Intermediate Radioactive Waste Repositoriesmentioning
confidence: 99%
“…Sielicki et al (1978a) isolated a mixed culture which could degrade styrene, and found that phenylacetic acid and 2-phenylethanol were present in the growth medium. Shirai and Hisatsuka (1979a) isolated…”
Section: Breakdown Via Phenylacetic Acidmentioning
confidence: 99%